ANALISIS PENGARUH HARGA, IKLAN DAN PENJUALAN PERSEORANGAN KREDIT USAHA RAKYAT (KUR) BANK BRI KCP LEMABANG TERHADAP KEPUTUSAN MEMINJAM OLEH PEDAGANG PASAR TRADISIONAL (STUDI KASUS DI PASAR LEMABANG, PALEMBANG) - Nyoman Tri Adnyani Sutama; Aslamia Rosa (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2014)
This research aims to determine the influence of price, advertise, and personal selling of Kredit Usaha Rakyat (KUR) BRI bank branch Lemabang on loan decision making of traditional market seller (a study case at Lemabang market, Palembang). The target population in this research is the traditional market seller at Lemabang market. Data collected from the questionnaires which distributed to 100 respondents. Sampling technique used was non probability sampling with accidental sampling method. The analysis technique used was multiple regression analyis. Based of reliability and validity testing, variable of advertise is not fulfill the requirement of reliability and validity, so this variable excluded to the next research. The result of this study indicates that price and personal selling have a positive influence and signficant on loan decision making.Keywords : Price, advertise, personal selling, KUR, loan decision making, seller.